New horizons in low oxidation state group 2 metal chemistry - Rösch, Bastian; Harder, Sjoerd (Chemical Communications, 2021)
Since the seminal report on Mg in the +I oxidation state in 2007, low-valent complexes featuring a Mg-I-Mg-I bond developed from trophy molecules to state-of-the-art reducing agents. Despite increasing interest in low-valency of the other group 2 metals, this area was restricted for a long time to a rare example of a Ca-I(arene)Ca-I inverse sandwich. This feature article focuses on the most recent developments in the field, highlighting recent breakthroughs for Be, Mg and Ca. The more exotic metal Be was the first to be isolated as a zero-valent complex which could be oxidized to a Be-I species. There also has been interest in breaking the Mg-I-Mg-I bond with superbulky beta-diketiminate ligands (BDI) that suppress (BDI)Mg-Mg(BDI) bond formation. This led to Mg-Mg bond elongation or Mg-N bond cleavage. Several reports on attempts to isolate (BDI)Mg radicals by combinations of ligand bulk, addition of neutral ligands or UV(vis) irradiation led to reduction of the aromatic solvents, underscoring the high reactivity of these open shell species. Only recently, zero-valent complexes of Mg were introduced. Double reduction of a (BDI)MgI complex with Na gave [(BDI)Mg-]Na+. This Mg-0 complex crystallized as a dimer in which the Na+ cations bridge the two (BDI)Mg- anions which react as Mg nucleophiles. Thermal decomposition led to spontaneous formation of Na-0 and a trinuclear (BDI)MgMgMg(BDI) complex. This mixed-valence Mg-3-complex is a prime example of the fleeting multinuclear Mg-n intermediates discussed on the way from Mg metal to Grignard reagent. Attempts to prepare low-valent Ca-I compounds by reduction of (BDI)CaI led to dearomatization of the arene solvents: (BDI)Ca(arene)Ca(BDI). Reduction in alkanes prevented this decomposition pathway but led to N-2 reduction and isolation of (BDI)Ca(N-2)Ca(BDI), representing the first example of molecular nitrogen fixation with an early main group metal. As the N-2(2-) anion reacts in most cases as a very strong two-electron reductant, LCa(N-2)CaL could be seen as a synthon for hitherto elusive Ca-I-Ca-I complexes. Theoretical calculations suggest that participation of Ca d-orbitals is relevant for N-2 activation. These most recent developments in low-valent group 2 metal chemistry will revive this area and undoubtly lead to new reactivities and applications.
CRIS-Team WoS Importer:2021-09-10